How Students Can Use Ai To Draft Professional Financial Summaries In English - Uktam kizi, Xasanova Sitora; Abduvafoyeva Rayhona kizi (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This topic explores how students can effectively use artificial intelligence (AI) tools to create clear, accurate, and professional financial summaries in English. It highlights the role of AI in improving writing quality, organizing financial data, and enhancing language skills. The study also considers the benefits and limitations of AI, emphasizing the importance of critical thinking and human oversight when interpreting financial information. By using AI responsibly, students can save time, reduce errors, and produce well-structured financial reports suitable for academic and professional contexts.